Structure, physical and mechanical properties of bronze castings obtained by continuous and centrifugal casting - E. I. Marukovich; V. A. Kharkov; I. O. Sazonenko; V. A. Kukareko; A. V. Kushnerov (Литьë и металлургия, 2020)
The influence of crystallization conditions (continuous and centrifugal casting) of small-sized BrА1Fe4Ni4 bronze castings on the structure, phase composition, and hardness was studied. It was found by metallographic and X-ray diffraction methods that the castings consist of (α + γ')-eutectoid, α phase and AlCu, Al2Cu3 intermetallic compounds. The matrix phase in the alloy, crystallized by centrifugal casting, due to its higher alloying with Al atoms, has an increased value of the crystal lattice parameter, compared with the case of continuous casting. The hardness of the casting obtained by centrifugal casting increases compared with continuous casting, which is due to the formation of a more dispersed structure, as well as a large solid solution hardening of the matrix phase of the casting.